Edukasi Dan Sosialisasi Pasar Modal Pada Pelajar SMA/SMK Kota Padang - Murnati, Murnati; Rahmaita, Rahmaita; Raflis, Ratnawati Rachmat; Thahirah, Khadijah Ath; Indrayeni, Indrayeni; Wijaya, Riani Sukma; Mendrofa, Anes Hendry (Jurnal Pengabdian Masyarakat Dharma Andalas, 2025)
The capital market plays an important role in Indonesia's economy. However, with the rise of fraudulent investments, financial literacy education among the public, especially the younger generation, remains insufficient. This community service activity aims to enhance the understanding of high school students in Padang regarding the capital market and encourage them to invest wisely. Partners in this activity include SMK DEK, SMK Nusatama, SMAN 5, and SMAN 16 Padang, along with the Investment Gallery of BEI as facilitators. The methods used include lectures and demonstrations, with the hope of increasing the number of young investors. This education is expected to assist the Financial Services Authority (OJK) in improving financial literacy in the capital market sector.